Evaluation of hematological parameters and hemodialysis outcomes in patients with chronic kidney disease from north Gujarat: A prospective study - Deepika Modi; Jayesh Modi; Premaram Chaudhary; Sunita Dinkar Dinkar (Tropical Journal of Pathology and Microbiology, 2021)
ABSTRACTBackground: As chronic kidney disease (CKD) progresses the changes in hematological parameters become more evident. The present study aimed to determine the changes in hematological parameters and to evaluate effect of hemodialysis on the levels of serum creatinine and urea in patients with CKD from north Gujarat.Materials and methods: A prospective cross-sectional study conducted in patients with CKD who were on hemodialysis, age between 30 to 70 years, serum creatinine level more than 1.5 mg/dL. The hematological tests were carried out in 50 patients with CKD and they were compared with 50 age and sex matched controls. All hematological parameters were measured. Serum creatinine and urea were estimated before and after hemodialysis.Results: The mean age and gender was comparable between the groups. The hemoglobin, red blood cell count, packed cell volume, mean cell volume, mean cell hemoglobin, mean cell hemoglobin concentration and platelets were significantly lower in CKD group compared to control group (P<0.05). However, the mean neutrophil, lymphocyte, monocyte, and eosinophil count were significantly higher in patients with CKD compared to controls (P<0.05). The mean serum creatinine was higher in CKD group and significantly reduced after hemodialysis (11.61 mg/dL vs. 5.53 mg/dL; P<0.0001). Similarly, the mean urea concentration was higher in CKD group and significantly reduced after hemodialysis (143 mg/dL vs. 38.47 mg/dL; P<0.0001).Conclusion: Hematological parameters can be used as markers in patients with CKD and hemodialysis is an effective treatment in reducing serum creatinine and urea in patients with renal failure from north Gujarat.Keywords: hemoglobin, renal failure, post-hemodialysis, hemoglobin